Factors Related Of Anemia In Adolescence Girl - Rizky Vaira; Merlin Karinda; Muflihah (Science Midwifery, 2022)
Anemia during adolescence has a negative effect on growth, cognitive abilities, performance abilities and has a serious impact throughout the reproductive years. The study aims to determine the factors associated with the incidence of anemia in adolescent girls. This type of research method is a cross-sectional study. The sample in this study were female students of class XI and XII at SMAS PGRI 2 Banjarmasin who met the inclusion criteria totaling 75 people. Sampling technique with Total Sampling. The research instrument used measurements and questionnaires consisting of Body Mass Index (BMI), Middle-Upper Arm Circumference (MUAC), menstrual patterns and eating patterns. Data analysis using a computer program. The results showed that the female adolescents in SMAS PGRI 2 Banjarmasin who did not experience anemia were (70.7%) while the female adolescents who had anemia were (29.3%). There is a relationship between BMI and the incidence of anemia in adolescent girls p-value 0.023 (<0.05), there is a relationship between MUAC and the incidence of anemia in adolescent girls p-value 0.012 (<0.05), there is a relationship between diet and the incidence of anemia in adolescent girls p-value 0.021 (<0.05), there is a relationship between menstrual patterns with the incidence of anemia in adolescent girls p-value 0.026 (<0.05). Preventive and promotive efforts need to be done by increasing the consumption of nutritious food and giving blood-supplementing tablets especially for female students.